2011
DOI: 10.1590/s1413-70542011000400014
|View full text |Cite
|
Sign up to set email alerts
|

Efeito antioxidante da ficocianina em pescado salgado-seco

Abstract: RESUMOA conservação e o armazenamento de alimentos com elevados teores lipídicos podem conduzir ao desencadeamento do processo oxidativo, causando modificações nas características sensoriais e redução da vida útil dos mesmos. A ficocianina é um pigmento extraído da microalga Spirulina platensis que apresenta propriedades antioxidantes, por isso, objetivou-se verificar o efeito antioxidante da ficocianina durante o armazenamento do pescado salgado. O pescado salgado foi produzido com o peixe Pacu (Piaractus mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Thus, microalgae ethanolic extracts were added to rainbow trout fillets that were then packaged in polyethylene bags and kept at 4 ºC up to 16 days (Taghavi Takyar et al 2019); as a result, lower peroxide and thiobarbituric acid indices were detected in treated fish fillets. Furthermore, phycocianin obtained from S. platensis showed antioxidant properties in dried-salted fish (Pacu, Piaractus mesopotamicus) during a 60-day storage time at 25 ºC (Bertolin et al 2011). The antioxidant properties of S. platensis extracts have also been proved in different kinds of non-marine foods such as yogurt (Barkallah et al 2017), sausage (Luo et al 2017) and snacks (Lucas et al 2018).…”
Section: Analysis Of Lipid Damage Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, microalgae ethanolic extracts were added to rainbow trout fillets that were then packaged in polyethylene bags and kept at 4 ºC up to 16 days (Taghavi Takyar et al 2019); as a result, lower peroxide and thiobarbituric acid indices were detected in treated fish fillets. Furthermore, phycocianin obtained from S. platensis showed antioxidant properties in dried-salted fish (Pacu, Piaractus mesopotamicus) during a 60-day storage time at 25 ºC (Bertolin et al 2011). The antioxidant properties of S. platensis extracts have also been proved in different kinds of non-marine foods such as yogurt (Barkallah et al 2017), sausage (Luo et al 2017) and snacks (Lucas et al 2018).…”
Section: Analysis Of Lipid Damage Developmentmentioning
confidence: 99%
“…Additionally, bioactive compounds obtained from S. platensis including proteins (phycobiliproteins), pigments and phenolic compounds, among others, have been tested successfully to prepare preservative and novel biofilms (Larrosa et al 2018;Goettems Kuntzler et al 2018). Concerning marine products preservation, the employment of S. platensis extracts can be considered as scarce, previous research being limited to the potential antimicrobial effect against fish bacterial pathogens (Nanthini Devi et al 2016) and their antioxidant properties during rainbow trout (Oncorhynchus mykiss) refrigeration (Taghavi Takyar et al 2019) and during storage of dried-salted fish (Bertolin et al 2011). Furthermore, both antimicrobial (Najdenski et al 2013) and antioxidant (Romay et al 2001) activities have previously been reported for proteins from S. platensis.…”
Section: Introductionmentioning
confidence: 99%
“…Beneficial 69 effect of CPC (and/or its source spirulina) has been observed in var- 70 ious human disease models like Parkinson's [9], Multiple Sclerosis 71 [10] and Amyotrophic lateral Sclerosis [11]. CPC was also found to 72 confer protection in experimentally induced neurodegeneration 73 models of kainate and monosodium glutamate exposure [12,13]. 74 CPC was found to alter the expression of NMDA and inflammatory 75 genes [14] and dietary intake of Spirulina was found to be benefi- 76 cial in ischemic condition [15].…”
mentioning
confidence: 98%
“…The results obtained in the present study show that, due to the presence of phenolic compounds and their antioxidant activity, which are not degraded during the heat treatment, the spices contained in the herbal salt have a positive effect in the inhibition of the lipid oxidation of the roasted Dolphinfish, when compared to the pre-treated with refined salt ( Table 3). The use of refined salt in greater quantity, on the other hand, may have intensified the lipid oxidation reaction, due to its pro-oxidant action (Bertolin et al, 2011;Belitz et al, 2012;Mariutti & Bragagnolo 2017), influencing the degradation of monounsaturated and polyunsaturated fatty acids in the roasted fish. These results are compatible with the findings of Lira et al (2020), in which it was detected that bioactive substances from herbs had an antioxidant action on the fatty acid profile in roasted fish.…”
Section: Fatty Acid Profilementioning
confidence: 99%